Solar photodegradation of dichloroacetic acid and 2,4-dichlorophenol using an enhanced photo-Fenton process - Nogueira, Raquel Fernandes Pupo [UNESP]; Trovó, Alam G. [UNESP]; Modé, Daniela F. [UNESP] (Elsevier, 2002)
The photo-Fenton process using potassium ferrioxalate as a mediator was investigated for the photodegradation of dichloracetic acid (DCA) and 2,4-dichlorophenol (DCP) in aqueous medium using solar light as source of irradiation. The influence of the solution depth, the light intensity and the effect of stirring the solution during irradiation process were evaluated using DCA as a model compound. A negligible influence of stirring the solution was observed when the concentration of ferrioxalate (FeOx) was 0.8 mM and solution depth was 4.5 or 14 cm. The optimum FeOx concentration determined for solution depths between 4.5 and 14 cm was 0.8 mM considering total organic carbon (TOC) removal during DCA irradiation. The high efficiency of the photo-Fenton process was demonstrated on summer days, when only 10 min of exposition (around noon) were sufficient to completely destroy the organic carbon of a 1.0 mM DCA solution in the presence of 0.8 mM FeOx and 6.0 mM H2O2 using a solution depth of 4.5 cm. It was observed that the photodegradation efficiency increases linearly with the solar light intensity up to values around 15 Wm-2 but this linear relationship does not hold above this value showing a square root dependence. The photodegradation of a solution of DCP/FeOx showed a lower TOC removal rate than that observed for DCA/FeOx, achieving ∼90% after 35 min irradiation under 19 Wm-2, while under this light intensity, the same TOC removal of DCA/FeOx was achieved in only 10 min irradiation. © 2002 Elsevier Science Ltd. All rights reserved.
Keywords: Advanced oxidation processes; Ferrioxalate; Seasonal variation; Solar light intensity; Irradiation; Phenols; Photodegradation; Potassium compounds; Solar radiation; Photo-fenton process; Organic acids; 2,4 dichlorophenol; dichloroacetic acid; ferric ion; ferrous ion; oxalic acid derivative; 2,4-dichlorophenol; anthelmintic agent; chlorophenol; ferrioxalate; aqueous solution; degradation; Fenton reaction; irradiation; stirring; chemical reaction; decomposition; light; oxidation; photodegradation; pollutant; seasonal variation; solar radiation; total organic carbon; waste water management; chemistry; photochemistry; season; sunlight; Anthelmintics; Chlorophenols; Dichloroacetate; Oxalates; Photochemistry; Seasons; Sunlight; Support, Non-U.S. Gov't